Nutrition Education Videos: Influence on Fruit and Vegetable Consumption and Prevention of Childhood Obesity - Al Insyirah, Thifal Hazimah; Wahyuningsih, Utami; Andriyani, Reni (CV. Era Digital Nusantara, 2026)
The imbalanced nutritional status in children can negatively affect their health, growth, development, and ability to carry out daily activities. Nutritional problems in children, represent a significant challenge that requires focused attention due to the continuous increase prevalence. Dietary patterns, such as inadequate intake of vegetables and fruits, increase the risk of nutritional issues. Most school-aged children tend to be selective and avoid certain types of vegetables and fruits due to a lack of knowledge regarding their importance. Therefore, the aim of health education is to increase children's knowledge, encourage them to adopt healthier eating habits, and improve vegetable and fruit consumption behaviors. The “MASAYBU (Let's Eat Vegetables and Fruit) Every Day” program has targeted school-aged children (6-12 years old) through delivering information by video. It was implemented as a strategy to address obesity and enhance awareness of the importance of daily vegetable and fruit consumption. The program was attended by 31 children from a primary school within the UPTD Puskesmas Cinere area. A Wilcoxon test using IBM SPSS Statistic version 25 was conducted to evaluate the difference in knowledge before and after the intervention. The analysis showed p-value=0.000 (p<0.05), indicating that the “MASAYBU” educational video significantly improved children's knowledge of the importance of daily vegetable and fruit intake. The results demonstrate that the educational intervention effectively enhanced awareness and knowledge about daily vegetable and fruit consumption among school-aged children.